Investigation of the effect of cooling and delays as well as CO2 concentrations during storage on internal browning in 'Fuji' apples - Kriegler, Anmari (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.